The Increase of Private Forest's Role to Support Food Security and Proverty Alleviation (Case Study in Nanggung District, Bogor Regency) PENINGKATAN PERAN HUTAN RAKYAT DALAM MENDUKUNG KETAHANAN PANGAN DAN PENANGGULANGAN KEMISKINAN - Dwi Apriyanto; Hardjanto .; Yulius Hero (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
Forest has a potency to support food security and overcome poverty. This study was expected to measure the contribution of private forest and design a strategy to increase the role of private forests in food security and proverty alleviation in Nanggung.The respondent consisted of 60 private forest farmers. The qualitative and quantitative approach of this study revealed that private forest contributed about 23 food plants species as household daily food support and about 35.68% as means to better income for proverty alleviation. The strategy to increase the role of private forest were: 1) to strengthen the institutional of farmer groups in the private forest for food security; 2) to provide subsidies for private forest development for food; 3) to utilize the abandoned land as private forest for food; 4) to establish business partnership in terms of seeding, planting, harvesting, and marketing; and 5) to conduct efficient forest product marketing.Key words: Private forest, food security, proverty